1995
DOI: 10.2307/1939345
|View full text |Cite
|
Sign up to set email alerts
|

Convariation of Spider Egg and Clutch Size: The Influence of Foraging and Parental Care

Abstract: The purpose of this study was to investigate the effects of body size, foraging mode, and parental care on the relationship between clutch size and egg size in spiders. Specifically, covariation of egg size and clutch size with body size was investigated, using data from the literature, in 156 species of North American spiders from 22 families. Variance in clutch size and egg size was found to be mainly attributed to differences among genera. I therefore conducted a comparative analysis at the generic level. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
62
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 21 publications
8
62
0
3
Order By: Relevance
“…The full linear mixed models included snow t , snow t21 , plot and all interaction terms and observations were weighted according to sample size within plot and year Climate and body size of a spider T. T. Høye et al 543 stronger response in body size of P. glacialis females to variation in timing of spring snowmelt than in males suggests that size is also a more important predictor of reproductive success in females than in males in this species. Egg mass production is likely to be limited by female size and hence larger females may produce more and/or larger eggs (Simpson 1993(Simpson , 1995. In the highly seasonal Arctic environment, a major determinant of reproductive success in males may be the timing of their final moult.…”
Section: Discussionmentioning
confidence: 99%
“…The full linear mixed models included snow t , snow t21 , plot and all interaction terms and observations were weighted according to sample size within plot and year Climate and body size of a spider T. T. Høye et al 543 stronger response in body size of P. glacialis females to variation in timing of spring snowmelt than in males suggests that size is also a more important predictor of reproductive success in females than in males in this species. Egg mass production is likely to be limited by female size and hence larger females may produce more and/or larger eggs (Simpson 1993(Simpson , 1995. In the highly seasonal Arctic environment, a major determinant of reproductive success in males may be the timing of their final moult.…”
Section: Discussionmentioning
confidence: 99%
“…Selection for increased reproductive effort might favor correlated selection on components of reproductive effort (Winkler and Wallin 1987;Roff 1992;Schwarzkopf et al 1999;Caley et al 2001;Czesak and Fox 2003). Consequently, parental care effort may be positively associated with egg and clutch mass (Shine 1978;Sargent et al 1987;Nussbaum and Schultz 1989), although such correlations are not always found (e.g., Simpson 1995;Ruber et al 2004). Nest attentiveness (percentage of time that parents sit on the nest incubating eggs) is an important component of reproductive effort that varies among songbird species (Martin 2002).…”
Section: Parental Carementioning
confidence: 99%
“…Egg mass varies among species in relation to body mass for diverse taxa (Rahn et al 1985;Saether 1987;Berrigan 1991;Poiani and Jermiin 1994;Simpson 1995). Body mass only explains part of egg mass variation, however, and both the extent and causes of residual variation remain unclear.…”
mentioning
confidence: 99%
“…The model proposed by Marshall & Gittleman (1994) for the relationship between fecundity and the mass of females predicts fewer egg-sacs for T. stenaspis than were recorded. That of Simpson (1995) predicts a smaller total fecundity and larger eggs than recorded. The low number of eggs per egg clutch and their small size in T. stenaspis is presumably a result of an interaction between the size of the eggs and morphological constraints of the abdomen.…”
Section: Discussionmentioning
confidence: 80%